2017
DOI: 10.1038/ejcn.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: The effect of L-arginine supplementation on body composition and performance in male athletes: a double-blinded randomized clinical trial

Abstract: The correct reference for reference 9 is:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, Bailey and colleagues [ 645 ] concluded that acute arginine supplementation reduced the oxygen cost of moderate-intensity exercise and increased tolerance to high-intensity training. Moreover, Pahlavani et al [ 646 ] supplemented male athletes with arginine in a double-blind fashion and concluded that arginine supplementation significantly increased sport performance. As it stands, most of the published literature that has examined the ability of arginine to operate in an ergogenic fashion has failed to report positive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bailey and colleagues [ 645 ] concluded that acute arginine supplementation reduced the oxygen cost of moderate-intensity exercise and increased tolerance to high-intensity training. Moreover, Pahlavani et al [ 646 ] supplemented male athletes with arginine in a double-blind fashion and concluded that arginine supplementation significantly increased sport performance. As it stands, most of the published literature that has examined the ability of arginine to operate in an ergogenic fashion has failed to report positive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, a double-blind, controlled, randomized study tested the effectiveness of 2 g arginine supplementation on performance of 56 soccer players during 45 days and found significant improvements in maximum oxygen consumption (VO2max) with subsequent performance increase [69]. Twenty-eight soccer players were selected and supplemented with 6 g arginine during 14 days, and their performance in the RAST protocol on six 35-m consecutive sprints with 10 s of active rest was tested.…”
Section: Argininementioning
confidence: 99%